Competitiveness Factors and MSME Performance: Insights from Jambi Province - Tona Aurora Lubis; Firmansyah, Firmansyah; Mukhzarudfa, Mukhzarudfa; Utama, Ahmad Nur Budi; Sari, Novita; Ningsih, Maryati (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the impact of competitiveness factors on MSME performance in Jambi Province. The research focuses on four key competitiveness factors: financial capabilities, entrepreneurial skills, government policies, and technological advancements. Utilizing a quantitative approach, data were collected from 100 MSMEs through structured questionnaires. The analysis was conducted using Partial Least Squares (PLS) through Smart PLS 3 software. The findings indicate that entrepreneurial skills are the most significant factor influencing MSME performance, with profit growth identified as a key performance indicator. These results suggest that enhancing entrepreneurial capabilities and leveraging regional strengths can improve MSME competitiveness and sustainability in both local and global markets.